Community Structure of Soil Invertebrates Under Differing Restoration Practices — Alluvial Diamond-Mined Sites in South Africa - Lyons, C.-L.; Picker, M.D.; Carrick, P.J. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
The use of invertebrates in assessing mining rehabilitation has long been a topic of discussion. The feasibility and use of invertebrates as indicators of restoration success is a valuable tool enabling ecologists to best restore a disturbed habitat as closely as possible to an undisturbed site of similar characteristics. This paper investigated the use of invertebrate larvae and soil fauna as tools for evaluating restoration success of alluvial diamond-mined sites in the Namaqualand region of South Africa. Two different sites, approximately 150 km apart were chosen for study and comparison. Four different treatments, each with four replicates was chosen at each of the sites. These were: old topsoil (> five years), young topsoil (< 4 years), overburden (mined but never restored) and baseline/reference sites. Different restoration techniques had been used at both the Northern and Western Cape sites and hence, the findings of this paper enable us to draw conclusions as to the effectiveness of these various techniques. Invertebrates were collected by two methods: emergence traps and sieving. Three emergence traps were placed at each replicate site and two areas were chosen for sieving. At both sites, undisturbed/reference sites were found to most closely approximate old topsoil sites (MDS plots) although the percentage similarity between these two treatments was only 16.6% for the Northern Cape (NC) site and 17.8% for the Western Cape (WC) site. A Kruskal-Wallis ANOVA detected a significant difference in number of species between the four different treatments (df = 3, H = 8.676, p = 0.0339 for the Western Cape and df = 3, H = 11.567, p = 0.0090 for the Northern Cape). At both the Northern and Western Cape sites, the average number of species was found to be greatest at baseline/reference sites, followed by old topsoil, young topsoil and overburden sites (OB) in that order. It seems likely that the most likely reason for invertebrate colonization may be soil parameters and not vegetation cover as both regions seem to share similar vegetation cover. On preliminary investigation, it seems also that many of the old topsoil sites (TPS) contain similar vegetation cover to the reference sites. It appeared that the topsoil treatments used at the Western Cape site seem to approximate more to the reference site than do those of the topsoil used at the Northern Cape site.